Minerals of bulk and fine-grained (2 µm) samples from DSDP Leg 60 - Latouche, Claude; Maillet, Noelle; Blanchet, R (Supplement to: Latouche, C et al. (1982): X-ray mineralogy studies, Deep Sea Drilling Project Leg 60. In: Hussong, DM; Uyeda, S; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 60, 437-453, https://doi.org/10.2973/dsdp.proc.60.119.1982, 1982)
A bulk-sediment and clay-fraction X-ray diffraction study of samples from Deep Sea Drilling Project Leg 60 shows an abundance of the following minerals: plagioclase feldspar, zeolite, smectite, Fe-Mg chlorite, attapulgite, and serpentine. Amorphous compounds are also abundant. The variations in abundance of the different components correspond to episodes of volcanic activity through time. Deposits from periods of great activity are composed of sediments very rich in amorphous matter and in "primary" minerals (e.g., plagioclase feldspars). During relatively quiet periods, clay minerals and zeolites predominate.